Growth and Maxillofacial Surgery - A Plea for a more Physiological Approach to Surgery - Delaire, Jean; Joos, Ulrich (Archive of Orofacial Data Science, 2024)
The present article is the unfinished final scientific work of the late Professor Jean Delaire and offers insights into his innovative ideas during the concluding phase of his career. Right at the beginning, Delaire challenges traditional teachings by asserting that all growth sites in the skeleton share the same histological origin, namely the cephalic neural ectomesenchyme. He advocates for a comprehensive understanding of biokinetic effects and sutural physiology beyond mere union elements. In addition, embryological, morphological, and biomechanical aspects are combined to present a comprehensive understanding of the development and evolution of maxillary and premaxillary structures in humans. Delaire argues that the development of the cranio-facial skeletal construct strictly adheres to universal laws governing harmonious and balanced states and highlights the adherence to universal mathematics in life while emphasizing that life does not accept fixity. Case presentations are used to demonstrate how orthopedic and surgical interventions are aimed at preventing, interrupting, and healing issues related to various growth sites in the facial skeleton, such as the premaxilla, tuberosity regions, mid-palatal suture, condylar region, and bony chin. These treatments also address soft tissue involvement, including masticatory muscles, nasolabial muscles, muscles affecting the chin, and soft palate muscles. Pioneering work by renowned anatomists accompanies and substantiates Delaire's explanations by tracing the historical development of these ideas, with the realization that the actual physiology of the sutures only became widely known in the orthodontic and maxillofacial world at a very late stage.